Feline pancreatic ducts are consistently identified on CT and more likely to be dilated in the body of pancreas in cats with elevated feline pancreatic lipase immunoreactivity. Issue 3 (2nd January 2020) - Park, Jae Yoon; Bugbee, Andrew; Sharma, Ajay; Secrest, Scott
Abstract: Feline pancreatitis is a challenge to diagnose and no previously published study has described the CT characteristics of the pancreatic duct (PD) in cats. The current prospective analytical study was performed to identify and describe the CT characteristics of the PD in normal cats and to compare that to those cats with an elevated feline pancreatic lipase immunoreactivity (fPLI). Contrast‐enhanced CT was performed in 16 normal cats and 13 cats with an elevated fPLI. Two ACVR‐certified radiologists blinded to the fPLI status assessed whether or not the PD could be identified, contrast phase during which the PD was most conspicuous, and PD shape in the body, right and left lobes. A second‐year radiology resident blinded to the fPLI status measured maximum PD diameter and PD:parenchyma. The PD was identified in 84 of 87 pancreatic segments, which was most conspicuous in the portal phase in 28 of 29 cats. The PD shape was tubular (48/84), tapered (34/84), or beaded (2/84) with no significant difference ( P = 1.0 to .1615) between groups. Mean maximal PD diameters of normal cats were 1.5‐1.7 mm, which was significantly larger in the body of the pancreas in cats with an elevated fPLI (2.4 mm, P = .0313). Mean PD:parenchyma was not significantly different between groups ( P = .2001 to .949). In conclusion, the feline PD can be consistently identified on CT, for which the portal phase is preferred. Cats with an elevated fPLI are more likely to exhibit dilation of the PD in the body of the pancreas on CT.